2015
DOI: 10.1120/jacmp.v16i3.5369
|View full text |Cite
|
Sign up to set email alerts
|

Tangent field technique of TomoDirect improves dose distribution for whole‐breast irradiation

Abstract: TomoDirect (TD) is an intensity‐modulated radiotherapy system that uses a fixed gantry angle instead of rotational beam delivery. Here, we investigated the effect of the multiple beam technique of TomoDirect on dose distribution compared with commonly‐used tangential beams. We included 45 consecutive patients with right breast cancer who underwent postoperative radiotherapy in our institute in the present study. Clinical target volume (CTV) was the whole right breast. The planning target volume (PTV) was creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…Overall, TD was significantly superior to all other techniques in terms of IL sparing. Compared to previous studies, IL mean values obtained from our study in G1 were 14.9 ± 5. similar for FiF [10,15,16,32], s-IMRT 2f [14][15][16]31], s-IMRT 4f [14,31,32], VMAT [10,[14][15][16] and HT [10,18,32] while for TD it was lower than those previously published [23,32]. Rotational techniques significantly increased the low dose spillage to the contra-lateral lung as highlighted in particular by the V5Gy values that still remained well below the dose constraints as well as the endpoint for radio-induced pneumonitis.…”
Section: Discussionmentioning
confidence: 54%
“…Overall, TD was significantly superior to all other techniques in terms of IL sparing. Compared to previous studies, IL mean values obtained from our study in G1 were 14.9 ± 5. similar for FiF [10,15,16,32], s-IMRT 2f [14][15][16]31], s-IMRT 4f [14,31,32], VMAT [10,[14][15][16] and HT [10,18,32] while for TD it was lower than those previously published [23,32]. Rotational techniques significantly increased the low dose spillage to the contra-lateral lung as highlighted in particular by the V5Gy values that still remained well below the dose constraints as well as the endpoint for radio-induced pneumonitis.…”
Section: Discussionmentioning
confidence: 54%
“…Advanced RT techniques, such as fixed-field IMRT (ff-IMRT), or further developments, such as TomoTherapy, now allow treating multiple target volumes with different prescribed doses in a single plan. Previous studies have demonstrated that IMRT and TomoTherapy outperformed conventional three-dimensional conformal radiotherapy (3DCRT) for the whole breast irradiation [6][7][8]. Several studies have already been published comparing various treatment modalities for PMRT treatment without the boost scheme [9][10][11] and the whole breast irradiation [8,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…For breast cancer patients, reducing the dose to OARs from radiotherapy treatments is important as the 10‐year survival probability for diagnosed stage I and II patients treated with radiation after breast‐conserving therapy is higher than 60% . Several studies have reported dose to the OARs from the different modalities available for radiation delivery including three dimensional conformal therapy (3D‐CRT), tomotherapy, static‐field intensity‐modulated radiation therapy (IMRT) and volumetric arc therapy (VMAT) …”
Section: Introductionmentioning
confidence: 99%